Insulin resistance disrupts white matter microstructure and amplitude of functional spontaneous activity in bipolar disorder. (20th November 2022) - Mazza, Elena; Calesella, Federico; Paolini, Marco; di Pasquasio, Camilla; Poletti, Sara; Lorenzi, Cristina; Falini, Andrea; Zanardi, Raffaella; Colombo, Cristina; Benedetti, Francesco
Abstract: Background: Bipolar disorder (BD) is linked to several structural and functional brain alterations. In addition, BD patients have a three‐fold increased risk of developing insulin resistance, which is associated with neural changes and poorer BD outcomes. Therefore, we investigated the effects of insulin and two derived measures (insulin resistance and sensitivity) on white matter (WM) microstructure, resting‐state (rs) functional connectivity (FC), and fractional amplitude of low‐frequency fluctuation (fALFF). Methods: BD patients ( n  = 92) underwent DTI acquisition, and a subsample ( n  = 22) underwent rs‐fMRI. Blood samples were collected to determine insulin and glucose levels. The Homeostatic Model Assessment for Insulin Resistance (HOMA‐IR) and quantitative insulin sensitivity check index (QUICKI) were computed. DTI data were analyzed via tract‐based spatial statistics and threshold‐free cluster enhancement. From rs‐fMRI data, both ROI‐to‐ROI FC matrices and fALFF maps were extracted. Results: Insulin showed a widespread negative association with fractional anisotropy (FA) and a positive effect on radial diffusivity (RD) and mean diffusivity (MD). HOMA‐IR exerted a significant effect on RD in the right superior longitudinal fasciculus, whereas QUICKI was positively associated with FA and negatively with RD and MD in the left superior longitudinal fasciculus, left anterior corona radiata, and forceps minor. fALFF was negatively modulated by insulin and HOMA‐IR and positively associated with QUICKI in the precuneus. No significant results were found in the ROI‐to‐ROI analysis. Conclusion: Our findings suggest that WM microstructure and functional alterations might underlie the effect of IR on BD pathophysiology, even if the causal mechanisms need to be further investigated.